Stress induced evolution of non-genotypic heterogeneity - Moreton, Katy V. (2017)
Genetically identical populations can exhibit a range of behaviours within a phenotype, despite sharing a genetic background. This is referred to as non- genotypic heterogeneity (NGH). NGH can be conferred by a heritable change in DNA that affects the noise surrounding expression of a protein product. Copper and zinc are trace metals that are essential for normal growth and development, but are toxic in surplus amounts. NGH in response to copper stress has previously been identified in wild yeast isolates, but this was not produced under standardised conditions. Can we reproduce the conditions from the environment to produce high NGH through a controlled experimental evolution?